(untitled) (Eurasian Journal of Philology Science and Education, 2020)
Compared to modern Kazakh, the language of Abay’s works has quite a few differences. These differences are studied in terms of phonetic, morphological and lexical features. One of these features is observed in the use of certain verbs by Abay. For example, in Abaу’s works, the verbs “bagu, tonu, kashyru, sagynu, salu”, etc. were used in their original meanings. The article analyzes the features of the use of the verb “qyl”, used in Abay’s poems and in the edification of “Kara sozder”. In this work, the examples reflect how and how many times Abay used the form “qyl”. Also, words, phrases, phraseological units formed from the verb “kylu” were compared with versions of the modern literary language as “zhasau” and “etu”. Statistics and comparisons of the use of this form with the auxiliary verbs “etu” and “zhasau”, which are actively used in the modern Kazakh language, are given. On the basis of comparative analysis with samples of oral literature, data from Turkic monuments and languages, it was proved that the verb “qyl” is a manifestation of the continuity of traditions used since ancient times. Key words: Abay, Abay’s works, verb, verb “qyl”, comparative analysis.